Hubungan Asupan Energi, Asupan Protein, dan Kadar Hemoglobin dengan Produktivitas Kerja Wanita Petani Kelurahan Tegalroso, Kabupaten Temanggung Tahun 2015 - Yhani Kartika Sukowati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Productivity is a comparison between the result that can be achieved with the overall resources used per unit of time. A worker defined as productive worker if he/she is able to produce more output than other workers for the same time unit. Productivity is determined by :the level of education, work discipline, motivation, physical condition, attitudes and habits, work environment, work methods, equipment used, attitudes and ethics, nutritional status, work experience, and years of working. The general objective of this study was to determine the correlation between energy intake, protein intake, and levels of hemoglobin with productivity of women farmers in Kelurahan Tegalroso, Kabupaten Temanggung, 2015.This research is a quantitative study with cross sectional design. The sample were 32 respondent taken by using purposive sampling technique. Energy and protein intake data obtained through Recall 2x24 hours on non consecutive days. Hemoglobin was measured using Quick Ckeck. The productivity is measured by calculating the area of land that can be cultivated by women farmers in unit of time. Analysis of data normality test using the Shapiro-Wilk and Pearson Product Moment Correlation.More than half of respondent (84%) belongs to a group of energy intake that is less than AKE. Most of the respondent (59%) belongs to a group of protein intake that is less than AKP. About 12% respondent are anemic and 50% are working in accordance with the standards. There is no correlation between intake of enegy, protein, and hemoglobin with productivity of woman farmer. (p = 0.403, p = 0.965 and p = 0.571)Based on theresearch, the authorssuggestthatthe inhabitant should pay attentionforfood intake. The farmers shouldbe more active inagriculturaltrainingtoimprove the quality ofagriculture. It also needs todomore research todetermineother factors thataffect theproductivity offarmers.